PEMANFAATAN PEMASARAN ONLINE UNTUK MENDUKUNG KEWIRAUSAHAAN DIGITAL DI DESA JATIMULTO - Nungky Viana Feranita (STKIP PGRI Sidoarjo, 2018)
This program aims to improve understanding of the target community in utilizing online marketing (social media, online platforms, applications, etc.) because it is important for MSMEs to go digital in order to further expand the reach of the MSMEs market. From the results of the activities carried out, it is known that the average MSMEs actors in Jatimulyo Village do not know about online marketing. During this time they only do offline marketing so that sales are less optimal and run slowly, their businesses are also less developed because of limited marketing in Jatimulyo and surrounding villages. Through this activity, MSMEs actors can utilize online marketing to support digital entrepreneurship in Jatimulyo Village.